Method design for distillers solubles recycling and reusing into fuel pellets - Shkop, Andrii; Shestopalov, Oleksii; Ponomarova, Natalііa; Tseitlin, Musii; Miroshnichenko, Denis; Lebedev, Vladimir; Chudovska, Tetiana; Ttembitskyi, Dmytro; Ivanenko, Dmytro; Miroshnychenko, Mikhailo (VÚRUP, 2025)
The perspectives for processing distillers solubles from external accumulators into fuel pellets are given in the article. The distillers solubles from Ukrainian distilleries physicochemical properties were researched. It was found that distillers solubles from external accumulators are polydisperse, contain solid particles and dry organic substances - 50-60 g/L with a 85-90 wt.% moister contain. The distillers solubles dehydration efficiency in laboratory and industrial conditions was investigated. It was shown that high distillers solubles efficiency dehydration is possible in Ecomash SHS centrifugal units with a biconical rotor profile, which allow separating undissolved particles and ensuring suspended substances sedimentation at the level of 81.8% in a two-phase mode (sediment and fugate) and up to 86.6% in a three-product mode (sediment, thickened product, fugate). The regularity of moisture release during the distillers solubles drying process has been studied. The possibility carrying distillers solubles dehydrated in centrifuges up to 10–14 wt.% moister contain, which is sufficient for granulated fuel pellets formation, has been shown. The obtained pellets calorific value has been determined, which for samples from different distilleries is 4600–5550 kcal/kg. To improve boiler operation workability, distillers solubles samples from different plants and fuel pellets have been studied. To reduce the ash melting point, it is recommended to add mineral components, for example, hydrolyzed phosphogypsum. Based on the research, a resource-saving technology for distillers solubles processing into pellets and a scheme of mechanical dehydration units using modern centrifuges have been developed.
Keywords: distillers solubles; fuel pellets; centrifuge; environmental; ecological safety; density; thermal drying; recycling of wastes; solid phases separation